Biocontrol and plant growth promotion potential of endophytic Bacillus subtilis JY-7-2L on Aconitum carmichaelii Debx. - Zou, Lan; Wang, Qian; Wu, Rongxing; Zhang, Yaopeng; Wu, Qingshan; Li, Muyi; Ye, Kunhao; Dai, Wei; Huang, Jing (Frontiers in Microbiology, 2023)
Aconitum carmichaelii Debx. is a famous medicinal plant rich in alkaloids and widely used to treat various human diseases in Asian countries. However, southern blight caused by Sclerotium rolfsii severely hampered the yield of A. carmichaelii. Beneficial microbe-based biological control is becoming a promising alternative and an environmentally friendly approach for the management of plant diseases. In this study, we evaluated the biocontrol potential of an endophytic bacterial strain JY-7-2L, which was isolated from the leaves of A. carmichaelii, against southern blight in vitro and by a series of field experiments. JY-7-2L was identified as Bacillus subtilis based on multi-locus sequence analysis. JY-7-2L showed strong antagonistic activity against S. rolfsii in vitro and on A. carmichaelii root slices by dual-culture assay. Cell-free culture filtrate of JY-7-2L significantly inhibited the hyphal growth, sclerotia formation, and germination of S. rolfsii. In addition, volatile compounds produced by JY-7-2L completely and directly inhibited the growth of S. rolfsii. Furthermore, JY-7-2L was proved to produce hydrolytic enzymes including glucanase, cellulase, protease, indole acetic acid, and siderophore. The presence of bacA, fenA, fenB, fenD, srfAA, and baeA genes by PCR amplification indicated that JY-7-2L was able to produce antifungal lipopeptides and polyketides. Field trials indicated that application of the JY-7-2L fermentation culture significantly reduced southern blight disease severity by up to 30% with a long-acting duration of up to 62 days. Meanwhile, JY-7-2L significantly promoted the fresh and dry weights of the stem, main root, and lateral roots of A. carmichaelii compared to non-inoculation and/or commercial B. subtilis product treatments. Taken together, JY-7-2L can be used as a promising biocontrol agent for the control of southern blight in A. carmichaelii.